Influência das condições meteorológicas na concentração de radônio em área de caatinga e mata atlântica dunar - Dantas, Vanessa de Almeida (Brasil, 2016)
The Radon (Rn-222) is a radioactive noble-gas, colorless, odorless, tasteless, dense (9.73 kg / m3) and highly soluble in water (solubility 1,67x10-4 25 ° C and 1 atm) that, except for carbon dioxide is the gas with greater solubility in the atmosphere. This study analyzed the variation and correlation of meteorological variables with the emanations of Radon and atmospheric ions in a rainforest environment and Caatinga in the state of Rio Grande do Norte, Brazil. Specifically, in Northeast biomes of Brazil (NEB) little is known about the Rn-222 behavior in relation to the distribution in the different levels of the lower troposphere, such as the Atlantic Forest Dune and Caatinga. The objective was to investigate the relationship between meteorological variables, atmospheric concentrations of Rn-222 and atmospheric ions to the period characterized as dry and rainy in the municipality of Apodi-RN and Parnamirim-RN in the dry season, entered in the biome Caatinga and Northeast Atlantic Forest Dune which covers about 800,000 km2 and 19,427 square kilometers respectively. The measurements were taken at 1.5 m above the ground. Collected from the air temperature data, relative humidity, wind speed and direction, atmospheric pressure and Rn-222 and atmospheric ion concentrations. The results showed bimodal pattern in the daily behavior of the concentration of Rn-222, in the early morning hours observed in every day. Similar behavior was observed for the concentration of ions between 04:00 and 05:00 HL (Local Time) in Parnamirim. In Apodi, the daily cycle of concentration of Rn-222 showed a pattern similar to Parnamirim, with a maximum principal of 29.38 Bq / m3 and 24.00 Bq / m3 during the dry and rainy seasons, respectively, around 17:00 HL and a secondary maximum at 15:00 HL with 27.37 Bq / m3 (dry season) and 19.00 Bq / m3 (rainy season). These cycles are consistent with conditions of a statically neutral atmosphere due to the periods of transition from stable to unstable regimes (first peak) and unstable stable ...